"Being seen" at the clinic: Zambian and South African health worker reflections on the relationship between health facility spatial organisation and items and HIV stigma in 21 health facilities, the HPTN 071 (PopART) study. (January 2019) - Bond, Virginia; Nomsenge, Sinazo; Mwamba, Monde; Ziba, Daniel; Birch, Alice; Mubekapi-Musadaidzwa, Constance; Vanqa, Nosivuyile; Viljoen, Lario; Pliakas, Triantafyllos; Ayles, Helen; Hargreaves, James; Hoddinott, Graeme; et al.
Abstract: Health workers in 21 government health facilities in Zambia and South Africa linked spatial organisation of HIV services and material items signifying HIV-status (for example, coloured client cards) to the risk of People Living with HIV (PLHIV) 'being seen' or identified by others. Demarcated HIV services, distinctive client flow and associated-items were considered especially distinguishing. Strategies to circumvent any resulting stigma mostly involved PLHIV avoiding and/or reducing contact with services and health workers reducing visibility of PLHIV through alterations to structures, items and systems. HIV spatial organisation and item adjustments, enacting PLHIV-friendly policies and wider stigma reduction initiatives could combined reduce risks of identification and enhance the privacy of health facility space and diminish stigma. Highlights: Spatial dimensions of stigma are linked to accessing HIV treatment in clinics. Distinct demarcation and client flow trigger visibility of People Living with HIV. Approaching HIV services carries a social risk of unwanted disclosure for PLHIV. Thoughtful spatial organisation and labelling reduces the chance of "being seen".